Magnon‐Coupled Intralayer Moiré Trion in Monolayer Semiconductor–Antiferromagnet Heterostructures. Issue 18 (31st March 2022) - Zhang, Yan; Kim, Heejun; Zhang, Wenjin; Watanabe, Kenji; Taniguchi, Takashi; Gao, Yanlin; Maruyama, Mina; Okada, Susumu; Shinokita, Keisuke; Matsuda, Kazunari
Abstract: Moiré fringe patterns created by stacking different 2D layered materials as artificial van der Waals (vdW) heterostructures have become a novel platform to study and engineer optically generated excitonic properties. The moiré patterns contribute to the formation of spatially ordered excitonic states (excitons and trions), which can be used in the quantum simulation of many‐body systems and ensembles of coherent quantum light emitters. The intriguing moiré excitonic properties are affected by and controlled via the interaction with magnetic elements. Here, a moiré excitonic system interacting with the magnetic elementary excitation of antiferromagnetic orders in MoSe2 /MnPS3 vdW heterostructures is reported. The low‐temperature photoluminescence spectra with additional fine spectral structures on the low‐energy side, which are coupled magnon–trion peaks below the Néel temperature of MnPS3, are carefully investigated. The fine spectral structures with long lifetime and coherence time are assigned to intralayer trion–magnon complexes trapped in the moiré potentials (moiré trion–magnon complexes). These findings highlight the emergence of moiré trion–magnon complexes and provide a new way to explore novel quantum phenomena in moiré excitonic systems with magnetic functionalities. Abstract : Moiré patterns of van der Waals heterostructures offer a powerful platform for engineering excitonic states, leading to the formation of moiré excitonic states. However, interactions between moiré excitonic states and magnetic elementary excitations are not studied. In this work, a moiré excitonic system interacting with an antiferromagnetic order in a monolayer MoSe2 and an antiferromagnetic MnPS3 heterostructure is reported.